Excessive unbound cefazolin concentrations in critically ill patients receiving veno-arterial extracorporeal membrane oxygenation (vaECMO): an observational study - Booke, Hendrik; Frey, Otto Roman; Röhr, Anka; Chiriac, Ute; Zacharowski, Kai; Holubec, Tomas; Adam, Elisabeth (Scientific reports, 2021)
The scope of extracorporeal membrane oxygenation (ECMO) is expanding, nevertheless, pharmacokinetics in patients receiving cardiorespiratory support are fairly unknown leading to unpredictable drug concentrations. Currently, there are no clear guidelines for antibiotic dosing during ECMO. This study aims to evaluate the pharmacokinetics (PK) of cefazolin in patients undergoing ECMO treatment. Total and unbound plasma cefazolin concentration of critically ill patients on veno-arterial ECMO were determined. Observed PK was compared to dose recommendations calculated by an online available, free dosing software. Concentration of cefazolin varied broadly despite same dosage in all patients. The mean total and unbound plasma concentration were high showing significantly (p = 5.8913 E−09) greater unbound fraction compared to a standard patient. Cefazolin clearance was significantly (p = 0.009) higher in patients with preserved renal function compared with CRRT. Based upon the calculated clearance, the use of dosing software would have led to lower but still sufficient concentrations of cefazolin in general. Our study shows that a “one size fits all” dosing regimen leads to excessive unbound cefazolin concentration in these patients. They exhibit high PK variability and decreased cefazolin clearance on ECMO appears to compensate for ECMO- and critical illness-related increases in volume of distribution.
Gesehen am 13.10.2021